Forward-looking Analysis of Financial Statements for Small and Medium-sized Enterprises in the Context of Digital Transformation - Can, Wu; Shuo, Wu (International Journal of Research in Interdisciplinary Studies, 2026)
In the era of digital transformation, small and medium-sized enterprises (SMEs) face unprecedented opportunities and challenges. Financial statements, as critical tools reflecting corporate performance and financial status, directly influence strategic decisions and sustainable competitiveness through their predictive analytical capabilities. This study focuses on forward-looking analysis of SME financial statements in the context of digital transformation, employing case analysis and literature review methodologies to systematically explore the impact of digitalization on financial statement analysis. First, through literature analysis, the theoretical foundations of digital transformation and financial management are systematically reviewed, clarifying the core concepts, phased characteristics, and impacts on financial statement structures and information disclosure. Second, selected SMEs across various industries and scales serve as case studies, where the case analysis method examines the evolving features of financial statements, the development of forward-looking indicator systems, and financial forecasting modeling, risk analysis, and scenario planning methods leveraging big data and cloud computing technologies. Third, the positive effects of digital transformation on SME financial management are analyzed, including real-time financial data processing, scientific financial decision-making, and enhanced risk prevention. Finally, innovative financial management strategies and implementation pathways are proposed to address bottlenecks such as funding constraints, technological barriers, and talent shortages encountered during digital transformation. The study reveals three key findings: (1) Digital transformation has shifted corporate financial statement analysis from post-event reviews to forward-looking forecasting; (2) Big data and cloud computing technologies provide robust technical support for financial forecasting in small and medium-sized enterprises (SMEs); (3) Resource constraints in SMEs' financial digital transformation require coordinated support from governments and society. This research offers theoretical references and practical guidance for SMEs to advance financial management digital transformation and enhance their financial forecasting capabilities.